Budaya politik Melayu bandar : kajian kes di Shah Alam - Mohd. Ibrahim, Abdul Latiff (2004)
This is a study of political culture. It discusses the political culture of urban Malays as manifested following the sacking of the Deputy Prime Minister who was also deputy UMNO president, Datuk Seri Anwar Ibrahim on 2 September 1998. This event gave rise, especially amongst the Malays, to a wave of protest and resistance that went on for a considerable long period - up to and beyond the general election of 1999. The 1999 election exhibited a striking shift in support from UMNO to opposition parties. UMNO faced its worst performance in that election. This study attempts to expose what caused the tremendous decline in support towards UMNO. Political culture here refers to the question of values. This study shows that the values held by the Malays had undergone a transformation to the extent that a wrong interpretation of these values had brought about UMNO's downfall. In the same context, certain values were found to have become more pronounced to the extent that the disregard shown to them had a negative impact upon UMNO. The sacking episode, leading to the people's discontent and the resistance that ensued; all these could be explained by referring to the values in the political culture. Due to the fact that resistance was more evident in the urban areas, specifically where Malay voters made up the majority, the city of Shah Alam therefore was chosen for this case study. The results show that the culture as represented in the values held had influenced the political choice of Malay voters during the 1999 election. In fact, not only were these values manifested through the vote in the election but these same values also explained actions prior to and following the event. The shift in political support away from UMNO is one of the many manifestations of the values held. In view of the fact that this shift is a form of resistance or protest, it follows that other actions taken like holding street demonstrations, distributing published materials or messages of resistance through leaflets or the internet, were all forms of overt resistance. All these forms of resistance are viewed here as resistance by the weak ( society in general) against thepowefil (the government or the authorities). The study therefore not only confirms the shift of support away from a party that all along had been enjoying it, but further shows how a series of resistance by the weak against the powerfkl had been sustained. This shift in support and the resistance that ensued was the result of a particular political culture.